2019
DOI: 10.1007/s11747-019-00663-9
|View full text |Cite
|
Sign up to set email alerts
|

Consumer effects of front-of-package nutrition labeling: an interdisciplinary meta-analysis

Abstract: As consumers continue to struggle with issues related to unhealthy consumption, the goal of front-of-package (FOP) nutrition labels is to provide nutrition information in more understandable formats. The marketplace is filled with different FOP labels, but their true effects remain unclear, as does which label works best to change perceptions and behaviors. We address these issues through an interdisciplinary meta-analysis, generalizing the findings of 114 articles on the impact of FOP labels on outcomes such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
256
4
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(298 citation statements)
references
References 73 publications
9
256
4
4
Order By: Relevance
“…Participants of low income, low education and with low nutrition knowledge had purchases with lower nutritional quality overall, across all labeling conditions. Somewhat and very knowledgeable 0.7 (2.9) −0.1 (2.7) 0.3 (3.5) p-trend 0.000 0.000 0.000 a The nutritional quality of the shopping cart was evaluated using the NPSC model Bolds indicate significant differences (p < 0.05) with GDA for a given characteristic level P-values indicate differences or linear trends across levels of a given characteristic for the corresponding label Scarce evidence exists on the effects of FOP labels in shopping environments and situations [41]. A recent review of literature reported that only interpretive FOP labels, such as WL or the MTL, were able to modify consumers' purchasing intentions [41].…”
Section: Discussionmentioning
confidence: 99%
“…Participants of low income, low education and with low nutrition knowledge had purchases with lower nutritional quality overall, across all labeling conditions. Somewhat and very knowledgeable 0.7 (2.9) −0.1 (2.7) 0.3 (3.5) p-trend 0.000 0.000 0.000 a The nutritional quality of the shopping cart was evaluated using the NPSC model Bolds indicate significant differences (p < 0.05) with GDA for a given characteristic level P-values indicate differences or linear trends across levels of a given characteristic for the corresponding label Scarce evidence exists on the effects of FOP labels in shopping environments and situations [41]. A recent review of literature reported that only interpretive FOP labels, such as WL or the MTL, were able to modify consumers' purchasing intentions [41].…”
Section: Discussionmentioning
confidence: 99%
“…While grouping low‐calorie dishes in a menu is not effective, posting the amount of calories of each dish, without grouping, results in lower‐calorie choices (Parker & Lehmann, ). When healthy and unhealthy food packages have information about healthy nutrients, both types of food are considered healthier, but providing this information is still effective as it only increases purchases of healthy items (Ikonen, Sotgiu, Aydinli, & Verlegh, in press). In addition, people show increased consumption intentions when calorie quantities are presented with “just‐below” versus round numbers (e.g., 99 vs. 100 calories) (Choi, Li, & Samper, ), which suggests that presenting round numbers helps curb consumption.…”
Section: The Mechanisms Behind Self‐controlmentioning
confidence: 99%
“…Diet-related health problems evidenced by the increasing number of food-linked diseases as well as the consumer concerns towards the growing industrialized food production have dramatically increased over the last decades [1][2][3][4][5]. This has raised the importance of nutritional information as a relevant criterion affecting consumers' food choices [1].…”
Section: Introductionmentioning
confidence: 99%
“…This growing interest is also signaled by the increasing number of food products on the market that feature health claims or other labels that consumers infer as beneficial to health (e.g., functional foods, organic products, clean labels, or local food) [9]. A typical way to convey information about the healthiness of food products is through the back-of-pack nutrition label [4,10,11]. concept related to integration of health behavior, attention to one's health, health information seeking and usage, personal health responsibility, and health motivation.…”
Section: Introductionmentioning
confidence: 99%